Note—A Note on “The Influence of Setup Time on Job Shop Performance” by Wilbrecht and Prescott - Aggarwal, Sumer C. (Management Science, 1973)
Comments and clarifications about paper [Wilbrecht, J. K., W. B. Prescott. 1969. The influence of setup time on job shop performance. Management Sci. 16 (4, December).].